Association between Sleep Quality and Periodontal Status: A Case-Control Study - Fatemeh Kamalian Mehrizi; Ameneh Hosseini Yekani; Fahimeh Rashidi Maybodi (Journal of Dentistry, 2025)
Statement of the Problem: In the literature, the relationship between sleep quality and periodontal diseases has been mentioned, but still there is a lack of consensus and a valid conclusion in the results obtained.Purpose: This study aimed to compare the sleep quality of patients with periodontitis and their healthy counterparts. The correlation between sleep quality score and age, gender, occupation, brushing pattern, and the severity of periodontal disease was also investigated.Materials and Method: This case-control study was conducted on 106 patients with periodontitis and 106 controls with healthy periodontium referring to the Periodontology Department of Yazd Dental School from December 2021 to April 2022. The sleep quality of the two groups was assessed by the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed by ANOVA, t-test, and linear regression to assess possible correlations between the sleep quality score and demographic variables, tooth brushing pattern, and presence of periodontitis and its severity (alpha=0.05).Results: Totally, 149 females (70.3%) and 63 males (29.7%) with the mean age of 34.17±8.29 years, participated in this study. The sleep quality score had no significant correlation with age, gender, occupation, or tooth brushing pattern (p> 0.05). However, the sleep quality had a significant correlation with periodontitis (OR= 1.15, CI 95%: 1.02-1.29, p= 0.01). The sleep quality score had no significant correlation with the severity of periodontal disease (p= 0.225).Conclusion: Sleep quality of patients with periodontitis was significantly lower than that of healthy controls.